Pengaruh Perlakuan Invigorasi pada Benih Kedelai Hitam (Glycine soja) terhadap Vigor Benih, Pertumbuhan Tanaman, dan Hasil - Sucahyono, Didik; Sari, Maryati; Surahman, Memen; Ilyas, Satriyas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
The objective of this research was to improve seed vigor, plant growth, and productivity of black soybean through seed invigoration treatment. The experiment was arranged in split-plot design. As the main plot, there were two black soybean varieties (Detam-1 and Detam-2) and as the sub-plot there were seed invigoration treatments applied (untreated control, matriconditioning, biofertilizer, matriconditioning plus biofertilizer). Matriconditioning was conducted using ratio of seeds to carrier (rice hull charcoal) to water of 9:6:7 (w/w/v) for 12 h in ambient room. For biofertilizer treatment, biofertilizer (consists of nitrogen-fixing bacteria, phosphate-solubilizing bacteria, fungicide-producing bacteria, and growth-regulator-producing endophytic bacteria) was applied just before planted by mixing seeds with 6.25 g biofertilizer (kg seeds)-1 and small amount of water. Matriconditioning plus biofertilizer was conducted by integrating the biofertilizer in matriconditioning. Results of the experiment showed that matriconditioning or matriconditioning plus biofertilizer improved germination percentage and rate of germination. Biofertilizer or matriconditioning plus biofertilizer improved vegetative growth. Although there was no significant effect of invigoration treatment on productivity, biofertilizer treatment produced seeds 15% higher than control, and matriconditioning treatment produced seeds 13% higher than control. Viability and vigor of harvested seeds were not affected by invigoration treatments, however, Detam-2 had higher viability and vigor than Detam-1 based on germination percentage, index vigor, and rate of germination. Keywords: biofertilizer, matriconditioning, rice hull charcoal, seed quality ABSTRAK